The Analysis of the Application of Sufficiency Economy in Boromarajonani College of Nursing, Surin - Chularee, Saranya; Roongroung, Komwat; Chiaranai, Chantira (วารสารวิจัยทางวิทยาศาสตร์สุขภาพ วิทยาลัยพยาบาลบรมราชชนนี จังหวัดนนทบุรี, 2013)
บทคัดย่อ ปรัชญาเศรษฐกิจพอเพียงเป็นปรัชญาที่พระบาทสมเด็จพระเจ้าอยู่หัวทรงพระราชทานให้กับพสกนิกรชาวไทยเป็นปรัชญาแห่งการดำเนินชีวิตอย่างสมดุล พอเพียงและมีสติ วิทยาลัยพยาบาลบรมราชชนนี สุรินทร์ เป็นหนึ่งในองค์กรที่น้อมนำหลักปรัชญาเศรษฐกิจพอเพียงลงสู่การปฏิบัติ โดยฝ่ายวิชาการได้สนับสนุนให้อาจารย์จัดการเรียนการสอนที่สอดแทรกปรัชญาเศรษฐกิจพอเพียง การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อสังเคราะห์งานวิจัยด้านการสอนสอดแทรกปรัชญาเศรษฐกิจพอเพียง ของวิทยาลัยพยาบาลบรมราชชนนี สุรินทร์ ประชากรที่ศึกษาเป็นงานวิจัยในชั้นเรียนซึ่งจัดทำขึ้นในปีการศึกษา 2550 จำนวน 6 เรื่อง เครื่องมือที่ใช้เป็นแบบสังเคราะห์งานวิจัยซึ่งเป็นแบบสำรวจข้อมูลเชิงคุณลักษณะ นำข้อมูลที่ได้มาวิเคราะห์โดยการแจกแจงความถี่ ร้อยละ วิเคราะห์เนื้อหาและจัดหมวดหมู่ พบว่างานวิจัยส่วนใหญ่ทำวิจัยในรายวิชาศึกษาทั่วไป (83 %) มีวัตถุประสงค์การวิจัยเพื่อพัฒนาการจัดการเรียนการสอนสอดแทรกปรัชญาเศรษฐกิจพอเพียงที่เน้น 5 องค์ประกอบ (พอประมาณ มีเหตุผล ภูมิคุ้มกัน ความรู้ คุณธรรม) วิธีการสอนที่ใช้ได้แก่ แผนผังความคิดรวบยอด (100 %) การเรียนรู้แบบร่วมมือ (83 %) การนำเสนอผลงานและร่วมวิพากษ์ (83%)การใช้กรณีศึกษา (33%) การเรียนรู้ในสถานการณ์จริง (33 %) และการจัดนิทรรศการ (17%) เครื่องมือที่ใช้ ได้แก่ตัวผู้วิจัยในการเก็บข้อมูลเชิงคุณภาพ (100 %) แบบบันทึกภาคสนาม (100%) แบบวัดการใช้เหตุผลเชิงจริยธรรม (17%)แบบวัดความพึงพอใจต่อการจัดการเรียนการสอน (17%) ส่วนคุณลักษณะผู้เรียนตามแนวคิดเศรษฐกิจพอเพียง ได้แก่ความพอประมาณ เป็นการใช้เวลาและจำนวนข้อมูลอย่างเหมาะสม ความมีเหตุผล เป็นความรอบคอบในการหาข้อมูลก่อนตัดสินใจ ภูมิคุ้มกัน เป็น การวางแผนการเรียนรู้และเตรียมความพร้อมก่อนเรียน ความรู้ เป็นหลักวิชาตามลักษณะวิชาและการประยุกต์ภูมิปัญญาชาวบ้าน คุณธรรม เป็นการใช้เหตุผลเชิงจริยธรรมในการตัดสินใจ การดูแลบุคคลโดยยึดหลักมนุษยชนและปัจเจกบุคคล ความรับผิดชอบในการทำงานที่มอบหมาย ซื่อสัตย์ในข้อมูล และแบ่งปันประสบการณ์ผลการวิจัยทำให้เห็นว่าหลักปรัชญาเศรษฐกิจพอเพียงสามารถบูรณาการลงสู่กิจกรรมการเรียนการสอนได้ และช่วยให้เกิดการพัฒนาคุณลักษณะบัณฑิตให้เป็นผู้ที่ดี เก่งและมีความสุข คำสำคัญ : การสังเคราะห์ความรู้; การสอนสอดแทรกปรัชญาเศรษฐกิจพอเพียง Abstract Sufficiency Economy, a philosophyproposed by the King of Thailand, guides peopleat all levels on matters concerning nationaldevelopment. There are 3 elements and 2conditions of sufficient economy: 1) moderation, 2)reasonableness, 3) self-immunity, 4) knowledge,and 5) ethics. Boromarajonani College of Nursing,Surin, has incorporated sufficient economy way ofthinking into administrative and research. Thisstudy aimed to identify how the philosophy wasincorporated into teaching and research. Methods:Notes of six completed studies conducted in 2007were reviewed and analyzed. A content analysisapproach was used in this qualitative synthesisstudy. Results: More than 83% of the researchstudies on teaching had incorporated sufficiencyeconomic within the general education curriculum,but only 16% had incorporated into the nursingcurriculum. Teaching techniques used includedconcept mapping (100%), cooperative learning(83%), presentation and critique (83%), case study(33%), authentic learning (33%) and exhibitions(17%). Instruments used for data collectionincluded researcher (to collected qualitative data)(100%), field notes (100%), decision makingmeasurement (17%), and perception scale (17%).Content analysis exhibited 83.33 % of the studiesreported that students spent appropriate time andfair amount data in learning. This reflected“moderation” by its definition. Sixty seven percentsreported that students developed decision makingskills practically and realistically reflecting“reasonableness”. Five of six studies (83.33%)reported that by reading books and doingassignments prior to class, students were able tounderstand the contents and aware of theimportance of preparing which reflected “selfimmunity”by its definition. Additionally, 100%reported students’ competency as fair to good.This reflected “knowledge”. All (100%) reportedattributes of ethics appeared in students’behaviors by observing in classes andassignments. Findings suggested that principle ofsufficient economy contributed the development ofstudents. The principle of sufficient economyshould be implemented throughout curriculum. Keywords: Content analysis; Sufficiency economy; Nursing Instruction.